Knee osteoarthritis patients with severe nocturnal pain have altered proximal tibial subchondral bone mineral density. Issue 9 (September 2015) - Burnett, W.D.; Kontulainen, S.A.; McLennan, C.E.; Hazel, D.; Talmo, C.; Hunter, D.J.; Wilson, D.R.; Johnston, J.D.
Summary: Objective: Our objective was to investigate relationships between proximal tibial subchondral bone mineral density (BMD) and nocturnal pain in patients with knee osteoarthritis (OA). Methods: The preoperative knee of 42 patients booked for knee arthroplasty was scanned using quantitative computed tomography (QCT). Pain was measured using the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and participants were categorized into three groups: 'no pain', 'moderate pain', and 'severe pain' while lying down at night. We used depth-specific image processing to assess tibial subchondral BMD at normalized depths of 0–2.5 mm, 2.5–5.0 mm and 5–10 mm relative to the subchondral surface. Regional analyses of each medial and lateral plateau included total BMD and maximum BMD within a 10 mm diameter core or 'focal spot'. The association between WOMAC pain scores and BMD measurements was assessed using Spearman's rank correlation. Regional BMD was compared pairwise between pain and no pain groups using multivariate analysis of covariance using age, sex, and BMI as covariates and Bonferroni adjustment for multiple comparisons. Results: Lateral focal BMD at the 2.5–5 mm depth was related to nocturnal pain ( ρ  = 0.388, P  = 0.011). The lateral focal BMD was 33% higher in participants with 'severe pain' than participants with 'no pain' at 2.5–5 mm depth ( P  = 0.028) and 32% higher at 5–10 mm depth ( P  = 0.049). There were no BMD differences at 0–2.5 mm from the subchondral surface. Conclusion: This study suggests that local subchondral bone density may have a role in elucidating OA-related pain pathogenesis.